Multiple hydrogen location in a vacancy region of a FCC iron-nickel-based alloy - Simonetti, Sandra Isabel (2010)
The interaction between four-hydrogen atoms and a FCC FeNi-based alloy ideal structure having a vacancy (V) was studied using a cluster model and a semi-empirical theoretical method. The energy of the system was calculated by the atom superposition and electron delocalisation molecular orbital (ASED-MO) method. The electronic structure was studied using the concept of density of states (DOS) and crystal orbital overlap population (COOP) curves. After a sequential absorption, the hydrogen atoms are finally positioned at their energy minima configurations, near to the vacancy. The energy difference for H agglomeration was also computed. The vacancy-Hn complexes become less stable for n > 3. The changes in the electronic structure of Fe and Ni atoms near to the vacancy were also analysed. The interactions mainly involve Fe and Ni, 4s and 4p atomic orbitals. The contribution of 3d orbitals is much less important. The Fe-Fe, Fe-Ni and Ni-Ni bonds are weakened as new Fe-H, Ni-H and H-H pairs are formed. The effect of the H atoms is limited to its first neighbours. The detrimental effect of H atoms on the metallic bonds can be related to the decohesion mechanism for H embrittlement.